Viability of the Political System: A Neglected Issue in Public Finance - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2022)
The textbook theory of public finance delineates three primary functions of government: 1) to provide for public goods, 2) to provide for an equitable distribution of income, and 3) to stabilize the economy. However, it has become evident with the rise of right-wing populism especially, but not exclusively, in the U.S., that this conceptualization contains a crucial oversight of historic proportions because the gap between the haves and have-nots in a society is not merely a question of equity but also a question of the maintenance of political stability. The January 6, 2021 insurrection against the U.S. Congress by an angry mob made it evident that the distribution of income has bounds beyond which social forces exert such pressure on the political system that the whole edifice of liberal democracy is seriously threatened. Hence, democratic governments must consider income distribution also from the vantage point of sustaining itself.
Keywords: 330